Laggard clusters as slow learners, emerging clusters as locus of knowledge cohesion (and exclusion): A comparative study in the wine industry - Elisa Giuliani (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2004)
This paper adopts sociometric analysis to explore the process of knowledge acquisition and diffusion in clusters of firms. By comparing the knowledge systems of two clusters selected for being at different stages of their development path, this study shows that the knowledge system of the laggard cluster is weak, highly disconnected and vulnerable, while in the case of the emerging, dynamic cluster, the knowledge system is characterized by a more connected yet uneven knowledge acquisition and distribution process. These differences are then interpreted considering the heterogeneity of firm knowledge bases across and within clusters and the impact of this latter variable on the degree of intra- and extra-cluster connectivity is explored.
Keywords: O14; O30; L20; 330; clusters; firm knowledge base; knowledge systems; social network analysis; Wissen; Wissenstransfer; Regionales Cluster; Weinbau; Italien; Chile; Soziales Netzwerk